2015
DOI: 10.1534/g3.115.023564
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic and Gene Expression Profiles Exhibit Modular Genetic and Dietary Structure Linking Metabolic Syndrome Phenotypes in Drosophila

Abstract: Genetic and environmental factors influence complex disease in humans, such as metabolic syndrome, and Drosophila melanogaster serves as an excellent model in which to test these factors experimentally. Here we explore the modularity of endophenotypes with an in-depth reanalysis of a previous study by Reed et al. (2014), where we raised 20 wild-type genetic lines of Drosophila larvae on four diets and measured gross phenotypes of body weight, total sugar, and total triglycerides, as well as the endophenotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 55 publications
3
26
0
Order By: Relevance
“…Previous studies have associated genetic variation with metabolic phenotypes in human populations (Gieger et al 2008;Illig et al 2010;Suhre et al 2011;Shin et al 2014) and model organisms (Klenø et al 2004;Gilliland et al 2006;Keurentjes et al 2006;Martin et al 2007;Wentzell et al 2007;Schauer et al 2008;Fu et al 2009;Riedelsheimer et al 2012;Breunig et al 2014;Reed et al 2014;Williams et al 2015;Dumas et al 2016;Fernie and Tohge 2017;Swain-Lenz et al 2017). Disease-centered high dimensional multi-omic analyses have provided insight into the relationship between genetic variation and susceptibility to diseases (Hood et al 2004;Prabakaran et al 2004;Ibrahim and Gold 2005;Samuel et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have associated genetic variation with metabolic phenotypes in human populations (Gieger et al 2008;Illig et al 2010;Suhre et al 2011;Shin et al 2014) and model organisms (Klenø et al 2004;Gilliland et al 2006;Keurentjes et al 2006;Martin et al 2007;Wentzell et al 2007;Schauer et al 2008;Fu et al 2009;Riedelsheimer et al 2012;Breunig et al 2014;Reed et al 2014;Williams et al 2015;Dumas et al 2016;Fernie and Tohge 2017;Swain-Lenz et al 2017). Disease-centered high dimensional multi-omic analyses have provided insight into the relationship between genetic variation and susceptibility to diseases (Hood et al 2004;Prabakaran et al 2004;Ibrahim and Gold 2005;Samuel et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several studies from these researchers suggested that when populations were exposed to new environments, latent, or cryptic genetic variation was revealed that cannot be observed in long-term stable environments (Gibson & Reed, 2008; Reed et al, 2014, 2010). This may be particularly significant for diseases like MetS, insulin resistance, and T2D, for which dietary changes appear to have had large impacts on disease rates in human populations over a relatively short-time scale (Reed et al, 2014; Williams et al, 2015). Overall, these studies provide a wealth of information on the complexities of metabolic variation in flies that remains to be mined in the future and which will likely have high relevance for human populations.…”
Section: Drosophila As a Model For Metabolic Syndromementioning
confidence: 99%
“…We know the metabolome can vary greatly among genotypes within a species as well as across environments [25], and using genetically characterized models can assist in identifying the differences in the metabolome due to genetic and environmental effects (Figure 2). Many model organisms can be genetically engineered to test specific mechanistic questions, and panels of lines bearing mutations distributed across the model's genome are easily obtained ( e.g.…”
Section: Choosing a Model Organism And Genetic Systemmentioning
confidence: 99%
“…Some studies in flies have included a few tens of wild isolates, targeted toward capturing the variation among genotypes in the response to environmental factors. For example, Reed and colleagues quantified substantial genetic and dietary effects across 187 metabolites in a panel of 20 isofemale lines, and associated that variation with transcriptomic and disease phenotype variation [2,3]. Similar small-scale studies were conducted by Promislow and coworkers [38].…”
Section: Natural Isolatesmentioning
confidence: 99%
See 1 more Smart Citation